2018
DOI: 10.1007/164_2017_85
|View full text |Cite|
|
Sign up to set email alerts
|

Advancing Pharmacotherapy Development from Preclinical Animal Studies

Abstract: Animal models provide rapid, inexpensive assessments of an investigational drug's therapeutic potential. Ideally, they support the plausibility of therapeutic efficacy and provide a rationale for further investigation. Here, I discuss how the absence of clear effective-ineffective categories for alcohol use disorder (AUD) medications and biases in the clinical and preclinical literature affect the development of predictive preclinical alcohol dependence (AD) models. Invoking the analogical argument concept fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 279 publications
0
8
0
Order By: Relevance
“…Craving for alcohol can also be captured through cue-or stress-induction paradigm (Plebani et al, 2012). Together, these models produce measures of craving for alcohol that are either alcohol-induced, cue-induced, or stress-induced, which in turn parallels nicely with the preclinical literature on alcohol/drug reinstatement (Egli, 2018). Recent studies examining the factor structure of responses to an alcohol challenge suggested that alcohol craving is distinct from other dimensions of SR, namely stimulation, sedation, and negative mood (Bujarski et al, 2015b, Ray et al, 2009.…”
Section: Introductionmentioning
confidence: 78%
“…Craving for alcohol can also be captured through cue-or stress-induction paradigm (Plebani et al, 2012). Together, these models produce measures of craving for alcohol that are either alcohol-induced, cue-induced, or stress-induced, which in turn parallels nicely with the preclinical literature on alcohol/drug reinstatement (Egli, 2018). Recent studies examining the factor structure of responses to an alcohol challenge suggested that alcohol craving is distinct from other dimensions of SR, namely stimulation, sedation, and negative mood (Bujarski et al, 2015b, Ray et al, 2009.…”
Section: Introductionmentioning
confidence: 78%
“… 5 , 8 , 13 , 92 Both glucocorticoid receptors and CRF Subscript 1 receptors are being pursued as potential targets for AUD pharmacotherapies, but preclinical data in support of these targets have been generated primarily in males. 98 Recent work in male and female mice found that a history of alcohol drinking and intermittent PS exposure produced sexually divergent and brain region differences in protein levels for glucocorticoid receptors and CRF Subscript 1 receptors. 95 Increased cortical glucocorticoid receptor levels and hippocampal CRF Subscript 1 receptor levels were only found in female mice.…”
Section: Stress Steroids and Alcohol-related Behaviormentioning
confidence: 99%
“…AUD is also a heritable disorder, with a host of promising advances in understanding genetic causation and genetic predictors of treatment response 3,4 . While the past two decades have seen remarkable advances in our understanding of the neuroscience of addiction, 5,6 the translation of that knowledge to addiction therapeutics has been slower to materialize 7,8 . Efforts to improve this translation are timely in face of the BRAIN Initiative, which seeks to catalyze neuroscience discoveries to improve the treatment of neuropsychiatric disorders 9 .…”
Section: Introductionmentioning
confidence: 99%